Kepuasan kerja dalam kalangan operator pengeluaran - Nur Asilah, Mohd Taib (2015)
The workplace physical environment is the physical condition of an organization that is shared among workers to seek pleasure, comfort, satisfaction and safety as well as the impact on individual performance and motivation. It is proved it has a significant impact on job satisfaction. Factors that contribute to job satisfaction are ventilation, noise, lighting, layout, work space and so on. The point is to know whether the same factors existing in contributing to job satisfaction in the workplace in this research organization. Thus, this study aims to identify factors that contribute to job satisfaction in the Malaysia's employment context. In addition, this research measured the employee's perception of the workplace physical environment and job satisfaction. The population in this study are production operators in a manufacturing company that producing airplane components parts in Bukit Kayu Hitam, Kedah. 300 sets of questionnaires were distributed to respondents. Only 288 sets of questionnaires were used for data analysis. Generally, job satisfaction placed at a moderate level, while the level of employees' perception on the workplace physical environment also at a moderate level. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 20 to determine results for correlation and multiple regression analysis. The study also identified the direct relationship between the work place physical environment and job satisfaction. Overall, this study has shown that the layout and work space has a significant impact on job satisfaction among operator production, while the ventilation, noise and lighting does not have a significant impact on job satisfaction among production operators